Home range and habitat use of roan antelope Hippotragus equinus in Northern Botswana - Havemann, C.P.; Retief, T.A.; Collins, K.; Fynn, R.W.S.; Tosh, C.A.; de Bruyn, P.J.N. (Journal of arid environments, 2022)
Studies investigating animal movement and habitat use are essential for wildlife management and conservation. Northern Botswana represents some of the least modified landscapes in Africa. Studying the seasonal habitat use of herbivores in these landscapes provides important baseline information with which to compare the behavioural responses of similar species occurring in anthropogenically modified landscapes. We report on the home range extent and habitat use of roan antelope (Hippotragus equinus) in a region of northern Botswana unaffected by artificial water and fences. We deployed Global Positioning System (GPS) collars on individuals in four roan antelope herds in northern Botswana, three herds in the drier northern section of Botswana and one herd in the wetter Okavango Delta. Herds in the drier northern section occupied larger home ranges (>50 km2) than did herds in the wetter Okavango Delta (<50 km2). All herds preferred specific core areas (all smaller than 20 km2) within their home ranges. All herds had similar location and size of home range between the wet and dry season (non-migratory). All herds occurred in back-country sandveld areas dominated by either Kalahari apple-leaf (Philenoptera nelsii) or silver cluster-leaf (Terminalia sericea) woodlands with low densities of competitors and predators. In Botswana, the long-term persistence of free-roaming roan antelope herds likely depends on the preservation of these unmodified back-country habitats away from permanent water. [Display omitted] •First study to investigate the home ranges and habitat use of roan antelope in northern Botswana.•Study area is relatively unhindered by human intervention (i.e. no water provision, fences), providing a useful model system for understanding natural roan antelope habitat use through seasons.•Importance of ‘back-country’ habitats away from permanent water is highlighted for persistence of the species.•Management actions for conserving heterogeneity should not ignore ‘marginal’ habitats or those reflecting low abundance as these may be critical for maintaining rare species.